2016
DOI: 10.1097/md.0000000000005486
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative aspartate aminotransferase-to-platelet ratio index (APRI) is a predictor on postoperative outcomes of hepatocellular carcinoma

Abstract: Preoperative aspartate aminotransferase-to-platelet ratio index (APRI) has been identified as a biochemical marker for histological fibrogenesis and fibrosis in cirrhosis and prognosis of hepatocellular carcinoma (HCC). Whether preoperative APRI can predict postoperative short-term outcomes has not been studied. The purpose of this study was to investigate the ability of preoperative APRI to predict short-term outcomes following liver resection for HCC. APRI was evaluated in 360 patients undergoing liver resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 25 publications
1
34
1
1
Order By: Relevance
“…It is reported that serum APRI could be used in evaluating the degree of fibrosis and liver function reserve, as well as predicting prognosis for patients with chronic hepatitis [12]. APRI is also a predictor for postoperative outcomes of HCC [13]. In HBV-related HCC, Huang et al had reported that serum APRI might be employed as a biomarker for assessing liver cirrhosis and predicting both recurrence and survival of the patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that serum APRI could be used in evaluating the degree of fibrosis and liver function reserve, as well as predicting prognosis for patients with chronic hepatitis [12]. APRI is also a predictor for postoperative outcomes of HCC [13]. In HBV-related HCC, Huang et al had reported that serum APRI might be employed as a biomarker for assessing liver cirrhosis and predicting both recurrence and survival of the patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…The APRI was introduced by Wai et al in 2003 as a predictive measure for fibrosis and cirrhosis in patients with chronic hepatitis 25 . Later, different studies concluded that its preoperative measures significantly predict post-hepatectomy morbidity and mortality [26][27][28] . Mai et al recently evaluated 1,044 hepatocellular carcinoma patients that underwent liver resection, and demonstrated that APRI could significantly predict post-hepatectomy outcomes (AUC = 0.743), in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Ichikawa et al (25) confirmed that preoperative APRI independently predicts postoperative liver failure. In addition, Cheng et al (11) suggested APRI could predict postoperative complications in HCC patients after liver resection. Further, some studies confirmed that postoperative complications may adversely influence both postoperative RFS and OS for patients with HCC after liver resection (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…However, ALBI only reflects patient liver function and cannot indicate the degree of liver fibrosis in HCC patients. Preoperative aspartate aminotransferase (AST)-toplatelet count ratio index (APRI) has been confirmed as a surrogate marker for histological fibrogenesis (11). It is unclear whether ALBI incorporated with APRI results could strengthen the prognostic power for HCC patients within Milan criteria following liver resection.…”
mentioning
confidence: 99%